2016
DOI: 10.1007/s00355-016-0962-3
|View full text |Cite
|
Sign up to set email alerts
|

The political economy of (De)centralization with complementary public goods

Abstract: This paper provides a political economy analysis of (de)centralization when local public goods -with spillovers e¤ects -can be substitutes or complements. Depending on the degree of complementarity between local public goods, median voters strategically delegate policy to either 'conservative' or to 'liberal' representatives under decentralized decision-making. In the …rst case, it accentuates the free-rider problem in public good provision, while it mitigates it in the second case. Under centralized decision-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Consequently, the bargaining outcome is Pareto inefficient and, in some cases, even Pareto‐inferior to the outcome without negotiations. This is known as the strategic delegation problem (e.g., Besley & Coate, 2003; Buchholz et al, 2005; Cheikbossian, 2016; Dur & Roelfsema, 2005; Loeper, 2017; Segendorff, 1998). In our situation of an asymmetric role between regions, it has been shown that without a central government subsidy policy , the project does not reach the first‐best efficient level, even through negotiation (e.g., Gradstein, 2004; Loeper, 2015; Rota‐Graziosi, 2009; Shinohara, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the bargaining outcome is Pareto inefficient and, in some cases, even Pareto‐inferior to the outcome without negotiations. This is known as the strategic delegation problem (e.g., Besley & Coate, 2003; Buchholz et al, 2005; Cheikbossian, 2016; Dur & Roelfsema, 2005; Loeper, 2017; Segendorff, 1998). In our situation of an asymmetric role between regions, it has been shown that without a central government subsidy policy , the project does not reach the first‐best efficient level, even through negotiation (e.g., Gradstein, 2004; Loeper, 2015; Rota‐Graziosi, 2009; Shinohara, 2018).…”
Section: Introductionmentioning
confidence: 99%